1993
DOI: 10.1007/bf00188732
|View full text |Cite
|
Sign up to set email alerts
|

Organogenesis in the leech: development of nephridia, bladders and their innervation

Abstract: The formation of the definitive excretory system (nephridium and bladder complex) in Hirudo medicinalis during the last two thirds of embryonic development was observed with light- and electron microscopy, immunocytochemistry, and nuclear labeling. In jawed leeches, two excretory systems develop and function successively. The nephridia of the cryptolarva are associated with the larval sac and persist until the definitive nephridia are sufficiently developed to be functional. Development of the definitive excre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
1
19
1
Order By: Relevance
“…38,39 The bladders serve to store urine and nitrogenous wastes, primarily in the form of ammonia, prior to excretion. 33 Büsing et al in 1953 described two bacterial morphotypes closely associated with the nephridia and bladders and Wenning et al in 1993 showed that these symbionts were present and associated both intra-and extra-cellularly with the bladder during leech embryogenesis. 40,41 Further investigation into these relationships, however, was largely ignored until 2009 when they were investigated more thoroughly.…”
Section: Leech Endosymbiontsmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 The bladders serve to store urine and nitrogenous wastes, primarily in the form of ammonia, prior to excretion. 33 Büsing et al in 1953 described two bacterial morphotypes closely associated with the nephridia and bladders and Wenning et al in 1993 showed that these symbionts were present and associated both intra-and extra-cellularly with the bladder during leech embryogenesis. 40,41 Further investigation into these relationships, however, was largely ignored until 2009 when they were investigated more thoroughly.…”
Section: Leech Endosymbiontsmentioning
confidence: 99%
“…After hatching, the bacterial symbionts were not found to be present in adult leech bladders by TEM, suggesting that the bacterial symbionts do not play a critical role in the proper development of the nephridia and bladder. 41 Digestive tract. The seemingly simple question of who are the digestive tract symbionts of the leech has proven to be tricky.…”
Section: Leech Gut Anatomy and Feeding Behaviormentioning
confidence: 99%
“…Thus, the nature of the remaining cells is not known. However, since the peripheral neurons in leech are amenable to physiological (Blackshaw and Thompson, 1988;Wenning et al, 1993) as well as morphological studies In this composite micrograph of a hemisegment 9 hours further in development than the one in B, groups of neurons giving rise to all the peripheral neurons associated with the segmental nerves as well as the nephridal nerve cell (NNC) and HO3 cells are labeled by the Tractin-4F1 antibody. In addition, the first peripheral projection of the central neuron pioneering the dorsal-posterior (DP) nerve is clearly identifiable.…”
Section: Discussionmentioning
confidence: 99%
“…The cryptolarva transitions into a juvenile approximately midway into embryogenesis. The temporal acquisition of morphological attributes during embryonic development have been well described (3,12,16) (Fig. 1).…”
mentioning
confidence: 86%
“…An early culture-based study detected a bacterium that is now considered to be A. veronii in the cocoon albumen and in young leeches after hatching (1). In previous electron microscopy work investigating the embryonic development of the bladders, intracellular bacteria were detected within the bladder wall and extracellular bacteria within the lumen (2,16,17). A recent study revealed that this microbiota is organized in distinct layers and is composed of the deltaproteobacterium Bdellovibrio, betaproteobacteria Comamonas and Sterolibacterium, members of the Bacteroidetes, Sphingobacterium and Niabella, and alphaproteobacterium Ochrobactrum spp.…”
mentioning
confidence: 99%